Merdeka Curriculum and Merdeka Mengajar Platform to Improve Teacher Pedagogical Competence - Sabeliana, Devanda Martianta; Suryani, Mareta Dwi; Pratiwi, Tara; Hernina, Tifani Maya; Septihana, Vira Wahyu (JUPE : Jurnal Pendidikan Mandala, 2024)
The Merdeka Curriculum is one of the government's programs as a stepping stone in improving the quality of education. The Merdeka Curriculum provides freedom for educators to design learning as needed by students. The Merdeka Curriculum is a refinement of the 2013 Curriculum with several changes such as changing basic competencies and core competencies into learning outcomes, emphasizing formative assessments, and also providing freedom for educational units to develop operational curricula independently. The presence of the Merdeka Mengajar Platform also supports the implementation of the Merdeka Curriculum by providing digital resources to develop teacher professionals. This platform has a menu for Personal Development, Teaching, Inspiration and Information about the Merdeka Curriculum which can make it easier for teachers to obtain references, inspiration and understanding regarding the implementation of this curriculum. Implementation of the Merdeka Curriculum requires teachers to master pedagogical competencies such as understanding students, designing learning, implementing learning, evaluating learning outcomes, and developing student competencies. This research uses the literature study method. The results of this research show that the Merdeka Curriculum and Merdeka Mengajar Platform can increase the competence, innovation and creativity of teachers.